Trainer-advisor: the future that is already present - Juan Miguel Sánchez Ramón (Avances en Supervisión Educativa, 2014)
The dominant duo in the inspection function in recent years has been the control-supervision, in which everything is safe and inspector claimed status. The reality is quite different, but not completely lose sight of this postulate, the binomial is demanded as a result of the current functions of the inspection is the advisory-training. Strengthen by the new educational organization, despite its current wording postpones attack this reality, continuing the reference to a number of functions that include everything and nothing concrete. Therefore, this article is intended as a pretext for reflection and inspection in Spain really assess where you are and where you are going in the future that is already present.